Students views on STEAM-based mathematics learning - Aisyah, Nyimas; Arin, Arin; Susanti, Ely; Nuraeni, Zuli (Universitas Maritim Raja Ali Haji, 2024)
The 21st century demands educational approaches that align with technological advancements and societal needs. STEAM (Science, Technology, Engineering, Arts, and Mathematics) integrates multiple disciplines to foster critical thinking, creativity, communication, and collaboration in solving real-world problems. This study aims to explore ninth-grade students' perceptions of STEAM-based mathematics learning at SMP Negeri 13 Palembang. A mixed-method approach was employed, involving 94 students aged 13–15 years through questionnaires and unstructured interviews. Quantitative data were analyzed using Likert scale scoring, while qualitative data were assessed descriptively. Results indicate that students generally understand the concept of STEAM but lack clarity regarding its learning models, benefits, and assessment techniques. Most students (70.68%) perceived STEAM-based mathematics learning positively, finding it engaging, beneficial for understanding and retaining concepts, and motivating for further learning. Additionally, integrating technology and arts in mathematics increased student interest and participation. The study concludes that STEAM-based learning can enhance the effectiveness of mathematics education by creating a more interactive and meaningful experience for students. This approach equips students with essential 21st-century skills, making it a relevant strategy for future educational practices. Further studies are recommended to assess its long-term impact on student achievement and engagement.